Comparison Among Commonly Available Infant Formula Milks in the Iraqi Market - Ehab Mudher Mikhael MClinPharm (SAGE Publishing, 2015)
Breast-feeding is the best method of feeding infants. In some cases, formula milk can be a suitable alternative, so this study aimed to compare the safety and nutritional adequacy of commonly available formula milks in the Iraqi market. An observational study for the commonly available formula milks was conducted in the largest supermarkets of Baghdad, Iraq, during January-March 2015. The macronutrient and micronutrient contents as presented in the label of each type of formula milk was compared with the standard requirement of formula milk according to the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) guidelines. Dielac formula milk is the commonest formula milk in the Iraqi market, with the lowest price when compared with other formula milks. All infant formula milks (Similac, Guigoz, and S-26 Gold) except Dielac have the mandatory contents within the specified ranges, according to the ESPGHAN guidelines. Dielac lacks more than 1 of the major mandatory contents besides lacking all optional contents in its formula. Guigoz formula milk lacks the optional ingredients arachidonic acid, docosahexaenoic acid, and nucleotides. Similac milk was supplemented with a higher-than-specified level of nucleotides, and its l -carnitine contents were not declared. Only S26 Gold formula milk contained all mandatory and optional ingredients within the specified range, according to the ESPGHAN guidelines. In conclusion, no formula milk can resemble breast milk; however, S26 Gold formula milk is the most acceptable formula, and Dielac formula milk is the worst. Therefore, it is recommended that Dielac be withdrawn from the Iraqi market.